2016
DOI: 10.14814/phy2.13058
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polyphenols on cytokine and granulocyte response to resistance exercise

Abstract: This study examined the effect of resistance exercise on the production, recruitment, percentage, and adhesion characteristics of granulocytes with and without polyphenol (PPB) supplementation. Thirty‐eight untrained men were randomized into three groups: PPB (n = 13, 21.8 ± 2.5 years, 171.2 ± 5.5 cm, 71.2 ± 8.2 kg), placebo (PL; n = 15, 21.6 ± 2.5 years, 176.5 ± 4.9 cm, 84.0 ± 15.7 kg), or control (CON; n = 10, 23.3 ± 4.3 years, 173.7 ± 12.6 cm, 77.3 ± 16.3 kg). Blood samples were obtained pre (PRE), immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
(171 reference statements)
1
18
0
Order By: Relevance
“…The reliance on proxy serum markers of inflammation does not provide sufficient sensitivity to understand processes taking place within the damaged muscle itself. This point was clearly confirmed by Jajtner [ 128 ], since supplementation with a proprietary blend of green and black tea polyphenols suppressed IL8 protein expression in human skeletal muscle after intensive exercise, but there was no effect on circulating IL8 concentration. Myburgh et al [ 129 ] investigated the effect of grape seed-derived proanthocyanidolic oligomer (PCO) supplementation on the healing process after hindlimb contusion injury in male Wistar rats.…”
Section: Fruit-derived Polyphenols and Recovery After Intensive Exercsupporting
confidence: 58%
“…The reliance on proxy serum markers of inflammation does not provide sufficient sensitivity to understand processes taking place within the damaged muscle itself. This point was clearly confirmed by Jajtner [ 128 ], since supplementation with a proprietary blend of green and black tea polyphenols suppressed IL8 protein expression in human skeletal muscle after intensive exercise, but there was no effect on circulating IL8 concentration. Myburgh et al [ 129 ] investigated the effect of grape seed-derived proanthocyanidolic oligomer (PCO) supplementation on the healing process after hindlimb contusion injury in male Wistar rats.…”
Section: Fruit-derived Polyphenols and Recovery After Intensive Exercsupporting
confidence: 58%
“…IL-1ß, IL-6 and TNF-α. The juniper micro-emulsion was found to be rich in phenolic compounds including flavonoids which may be responsible for down-regulation of pro-inflammatory cytokines as studies have shown that flavonoids down-regulate inflammatory cytokines expression (Jajtner et al., 2016; Zeinali et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Herrlinger and colleagues [65] also reported that consumption of green tea polyphenols (2000 mg/day for 13 weeks) prior to downhill running (40 min, 65%VO 2 max) preserved muscle function, reduced circulating CK levels, and decreased soreness 48 h after exercise relative to placebo in recreationally active males. Conversely, several studies have shown that acute [66] and chronic [67] supplementation with tea-derived polyphenols did not attenuate the post-exercise flux of indirect markers of muscle damage after damaging resistance exercise. A later investigation [60] likewise found no effect of green tea extract supplementation (980 mg/day for 28 days) on markers of muscle damage in male sprinters who performed four repeated Wingate cycle sprints.…”
Section: Main Textmentioning
confidence: 99%